Food Policy Councils - J. Richman, Nessa (Taylor & Francis, 2026)
This book explains how Food Policy Councils solve critical food systems problems by creating just and resilient ways of producing, harvesting, manufacturing, distributing, and consuming food and managing food waste, using methods that encourage civic engagement and strengthen democratic processes. Although there are over 300 Food Policy Councils operating all across the United States, and scores in other countries, their critical work is not widely known. Due to the universal importance of food in people’s lives, Food Policy Councils represent an underutilized and underestimated tool to build community power and strengthen democratic engagement. The book presents a path forward for existing Food Policy Councils to grow their impact and shares tips for advocates planning to start new food policy councils. Success depends on several important skills: understanding how to bring people together across differences to find common ground, raising funds successfully for yourself and your stakeholders, and increasing community members’ abilities to advocate for changes in public policy and regulations. There are more and less successful ways to work to change the food system. This book will help food system leaders focus on the ones that work best, so Food Policy Councils can make a sustainable, significant impact. This book will appeal to professionals and researchers in the fields of food policy, food systems, governance and consumption, and anyone who is interested in civic engagement on matters involving food, nutrition and public health.